FAKTOR-FAKTOR PENYEBAB KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TENTANG SUDUT, BUSUR, DAN JURING DALAM LINGKARAN PADA SISWA KELAS VIII SMP NEGERI 21 KOTA BENGKULU - susanto, wawan adi; Muchlis, Effie Efrida; Maizora, Syafdi (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
AbstractThis study aims to: Determine the factors that causes students errors in solving about the angle, arc and juring in the circle of class VIII SMP Negeri 21 Kota Bengkulu This research uses qualitative descriptive method. Subjects in this study were students of class VIII 3 SMP Negeri 21 Kota Bengkulu. Data is processed through diagnostic tests and interviews. Data were analyzed descriptively. These result indicated that: The factors that cause errors students in solving problems circle as follows: a) Not understanding the concept on circle material as much as 28 students; b) Less careful in doing mathematics counting operations as many as 24 students; c) uessing the answers to as many as 11 students; and d) did not master the material prerequisites as many as 9 students